Pengembangan Modul Pembelajaran Bahasa Indonesia Materi Teks Persuasif Kelas VIII SMP Negeri 10 Kota Bengkulu - Lestari, Widia; Andra, Vebbi; Friantari, Heny (Yayasan Darusssalam Bengkulu, 2022)
This research belongs to the type of research and development (R&D). This study aims to develop an Indonesian language learning module for persuasive text material for class VIII SMP Negeri 10 Bengkulu City and to see the feasibility of an Indonesian language learning module for persuasive text material for class VIII SMP Negeri 10 Bengkulu City. Then the module is designed based on competency standards, basic competencies and syllabus in accordance with the 2013 curriculum. The module developed uses B5 paper size, Bookman Old Style font type, and 12 font size. In this study using the Borg and Fall theory which has 10 stages but the researcher simplifies it again into 7 stages namely potentials and problems, data collection, product design, design validation, revision of design validation results, product trials, and product revisions. The results of the product that has been developed are very feasible and interesting according to the results of the validation, validation involving 6 validators who are competent in their fields. Then this shows that the developed module is successful for use as teaching material. The advantage of this module is that it makes it easy for educators to teach persuasive text material and makes students enthusiastic about learning, the disadvantage is that it requires a fairly high cost because each student must have a module.